Covalent-linked porphyrin/single-walled carbon nanotube nanohybrids: synthesis and influence of porphyrin substituents on nonlinear optical performance. (November 2017) - Zhang, Mingfei; Fu, Lulu; Ye, Jun; Humphrey, Mark G.; Liu, Huan; Yan, Bing; Zhang, Long; Shao, Jianda; Zhang, Chi
Abstract: Electron-withdrawing 4-cyanophenyl-, electronically innocent phenyl-, and electron-donating 4-dimethylaminophenyl-functionalized porphyrin/single-walled carbon nanotube (SWCNT) nanohybrids have been synthesized and characterized by ultraviolet–visible absorption, steady-state fluorescence, Fourier transform infrared, and Raman spectroscopies, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy and thermogravimetric analysis. Nonlinear optical (NLO) studies using the Z-scan technique revealed that both the cyano (CN) and the dimethylamino (DMA) substituents have a positive effect in optimizing the optical limiting performance of the SWCNT–porphyrin nanohybrids, owing to increased reverse saturable absorption (RSA) of the porphyrin moieties after functionalization by CN or DMA. In comparison with CN, the DMA group has a more positive influence on the porphyrin excited states and thereby the RSA and NLO activity. Graphical abstract: